Reconstruction of the Cenozoic History of Hydrocarbon Fluids from Rifting Stage to Passive Continental Margin Stage in the Huizhou Sag, the Pearl River Mouth Basin - Yajun Li; Shu Jiang; Zhenglong Jiang; Hao Liu; Bingxi Li (Geofluids)
The Eocene lacustrine sediments are the primary source rocks in the Huizhou Sag of the Pear River Mouth Basin. This study employs basin modeling for four representative wells and two profiles in the Huizhou Sag to reconstruct the process of generation, expulsion, migration, and accumulation of hydrocarbon fluids. The Eocene source rocks started to generate hydrocarbon at 33.9 Ma and are currently in a mid-mature and postmature stage. Hydrocarbons are mainly expelled from the Eocene Wenchang Fm, and the contribution of the Eocene Enping formation is minor. Under the driving forces of buoyancy and excess pressure, major hydrocarbons sourced from the Eocene source rocks firstly migrated laterally to the adjacent Eocene reservoirs during the postrift stage, then vertically via faults to Oligo-Miocene carrier beds, and finally laterally to the structural highs over a long distance during the Pliocene-Quaternary Neotectonic stage, which is controlled by both structural morphology and heterogeneity of carrier beds. Fault is the most important conduit for hydrocarbon fluid migration during the Neotectonic stage. Reactivation of previous faults and new-formed faults caused by the Dongsha Movement (9.8–4.4 Ma) served as vertical migration pathways after 10.0 Ma, which significantly influenced the timing of hydrocarbon accumulation in the postrift traps.